2009
DOI: 10.15288/jsads.2009.s16.106
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Change Drinking Behavior in Female College Students

Abstract: ABSTRACT. Objective: Motivational interviewing (MI) therapies are effective in reducing high-risk drinking in college populations. Although research supports effi cacy of MI prevention strategies in reducing alcohol use, there are little data examining readiness to change (RTC), the underlying theoretical model of MI interventions. The purpose of the present study was to explore RTC variability and drinking behavior and whether MI increases RTC in an intervention group compared with controls. Method: Two-hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Still other studies have found no association between self-reported RTC and subsequent drinking (Borsari et al, 2009). As noted by Kaysen et al (2009), this inconsistency in results across studies likely reflects differences in the assessment of drinking outcomes (e.g., alcohol use quantity vs. frequency vs. consequences) or RTC (e.g., treating RTC as a static construct in cross-sectional studies vs. a dynamic construct in longitudinal studies), populations assessed (e.g., college students vs. treatment-seeking individuals), and/or differences regarding whether other relevant variables were incorporated into analyses (e.g., moderators of RTC-drinking behavior associations). Much of the work to date on this topic leaves unanswered a number of questions that are important to address to help advance research on the associations between RTC and drinking behavior.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Still other studies have found no association between self-reported RTC and subsequent drinking (Borsari et al, 2009). As noted by Kaysen et al (2009), this inconsistency in results across studies likely reflects differences in the assessment of drinking outcomes (e.g., alcohol use quantity vs. frequency vs. consequences) or RTC (e.g., treating RTC as a static construct in cross-sectional studies vs. a dynamic construct in longitudinal studies), populations assessed (e.g., college students vs. treatment-seeking individuals), and/or differences regarding whether other relevant variables were incorporated into analyses (e.g., moderators of RTC-drinking behavior associations). Much of the work to date on this topic leaves unanswered a number of questions that are important to address to help advance research on the associations between RTC and drinking behavior.…”
mentioning
confidence: 87%
“…To date, there has been a relative lack of this type of fine-grained research. In one important exception, Kaysen et al (2009) examined whether RTC predicted subsequent drinking behavior week to week over the course of 11 weeks in a sample of female college students. They found that on weeks when students reported more RTC relative to their average readiness levels, they also reported both intentions to drink less in the future and actual reductions in drinks per week the following week.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Motivational interviewing assumes that adherence of individuals to the treatment depends on their motivation, which can be changed throughout the treatment. 10 The stages of motivation are described in the literature [10][11] as follows: Pre-contemplation -people in this stage show little or no willingness to change and are often unaware they have a problem. Contemplation -this stage is evident when the individuals realize they have a problem and start thinking about future actions to make the change.…”
Section: Introductionmentioning
confidence: 99%
“…In MI it is understood that the relapse suggests an onward movement, the individual does not necessarily regress or remain in the same place, since they are more experienced and can integrate what they learned in the episode into their recovery process. 11 Motivational interviewing has been shown to be filled with characteristics that make it applicable with adolescents: the low cost of the treatment, easy access and training of the therapists, demonstrating high cost-benefit. 7 However, as proposed in 2005, 7 more systematized studies are still needed that prove the efficacy of this therapeutic method.…”
Section: Introductionmentioning
confidence: 99%